Analytical Plug-In Method for Kernel Density Estimator Applied to Genetic Neutrality Study. (21st July 2008) - Troudi Troudi, Molka Molka; Alimi Alimi, Adel M. Adel M.; Saoudi Saoudi, Samir Samir
Abstract : The plug-in method enables optimization of the bandwidth of the kernel density estimator in order to estimate probability density functions (pdfs). Here, a faster procedure than that of the common plug-in method is proposed. The mean integrated square error (MISE) depends directly uponJ ( f ) which is linked to the second-order derivative of the pdf. As we intend to introduce an analytical approximation ofJ ( f ), the pdf is estimated only once, at the end of iterations. These two kinds of algorithm are tested on different random variables having distributions known for their difficult estimation. Finally, they are applied to genetic data in order to provide a better characterisation in the mean of neutrality of Tunisian Berber populations.